(untitled) (Journal of Dhaka Medical College, 2015)
Objective: This study was carried out to improve day care transfusion facilities day by day as well as it is very time consuming and cost benefit both for patient and hospital authority, also government. Methods: According to instruction of the attending physicians, patients who were coming for day care transfusion all were recorded in prescribed data like name, age, sex, disease, number of transfusion ,transfusion reaction, etc. After proper cross matching and screening of donated blood, transfusion should be started, and monitor the patient every 15 minutes. If there is any transfusion reaction during or after transfusion, it should be noted and managed immediately. During this study, data was collected from record registered. Results: In this study, we found 742 patients were attended at Day Care Transfusion Center at DMCH, Dhaka, Bangladesh,in 2013. Among total patients male and female were 432 (58.23%)and 310 (41.77%) respectively. Age ranges of patients were 10-40 years 120 (16.17%) and 41-80 years 622 (83.82%).Among total patients, 548 (73.85%) were malignant. Other disease were aplastic anaemia, thalassaemia, myeloproliferative disease, Chronic kidney disease, Dysfunctional uterine bleeding, severe anemia due to unknown cause were 24(3.23%), 23(3.099%),50(6.73%), 43(5.79%),28(3.77%), 16 (2.15%) respectively J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 191-193